NRF-1 transcription factor regulates expression of an innate immunity checkpoint, CD47, during melanomagenesis - Makwana, Kuldeep; Velazquez, Edwin J.; Marzese, Diego M.; Smith, Bethany; Bhowmick, Neil A.; Faries, Mark B.; Hamid, Omid; Boiko, Alexander D. (Frontiers in Immunology, 2024)
Transmembrane integrin-associated protein CD47 functions as a potent innate immunity checkpoint and is upregulated by many types of malignant cells, including melanoma during tumor progression. Binding of CD47 to its target receptor, SIRPα, on myeloid cell lineages leads to the initiation of the downstream signaling cascades that inhibit innate immunity anti-tumor responses. Molecular mechanisms underlying upregulation of CD47 during melanoma progression remain largely unknown. In this report, we performed ATAC-Sequencing on patient-derived melanoma cells, as well as, the analysis of ATAC-Seq datasets covering clinical melanoma samples to demonstrate a significant increase in chromatin accessibility for the CD47 promoter region in comparison to normal cells and tissues. Additionally, profiling of multiple CD47 transcript isoforms established that upregulation of CD47 in malignant cells occurs at the mRNA level. Using chromatin immunoprecipitation (ChIP) approaches along with the analysis of ChIP-Seq cancer datasets, we identified the transcription factor NRF-1 which binds at multiple sites within the proximal CD47 promoter region. In combination with serial deletions of CD47 promoter, we defined the minimal DNA region required for its activation, as well as, specific DNA locations within that region, which are preferentially occupied by NRF-1 in tumor cells.